Pengaruh Pemberian PMT Bubuk Koya Berbahan Dasar Udang Rebon (Mysis relicta) terhadap Perubahan Kadar Hemoglobin Ibu Hamil - Vera Iriani Abdullah (EMBRIO: Jurnal Kebidanan, 2020)
Anemia in pregnancy, namely an Hb level of less than 11 g / dL or hematocrit, 33%, is still a global health problem, affecting nearly 50% of pregnant women, as well as a contributing factor to fetal and maternal morbidity. Iron tablets started early in pregnancy, according to WHO recommendations. However, in addition to the intake of blood-supplemented tablets, additional micronutrient intake is also needed by providing supplementation with foods containing iron. One of the animal food ingredients that meet multi micronutrients including iron, namely rebon shrimp because this is iron supplementation which is a source of animal food so that it is easier to absorb by the body. The purpose of this study was to analyze the differences in hemoglobin levels of pregnant women before and ingesting PMT koya powder made from rebon shrimp in the intervention and control groups. This type of research is a quantitative study with a quasi-experimental method using a posttest control group design approach. The results showed a p value of 0.000 <0.05, which is a significant difference between the control group and the intervention group. Conclusion the effect of PMT consumption of koya powder made from rebon shrimp on changes in hemoglobin levels of pregnant women.